Elites against democracy : leadership ideals in bourgeois political thought in Germany, 1890-1933 - Struve, Walter, 1935- (Princeton legacy library., 1973)
Since the beginning of the current era of imperialism in the late nineteenth century, there has been a striking contrast between bourgeois political thought in Germany and the West. Walter Struve demonstrates how German political culture went through a phase in which great emphasis was placed on the establishment of a new political elite recruited on the basis of merit and skill, but ruling in an authoritarian way, and not controlled by the populace. He suggests that this type of elitism, many aspects of which were vital to the political culture of Nazi Germany, seems today to be widespread i.